Foodborne parasites in the food supply web : occurrence and control - Gajadhar, Alvin A. (Woodhead Publishing in food science, technology, and nutrition ;, 2015)
Foodborne Parasites in the Food Supply Web: Occurrence and Control provides an overview of the occurrence, transmission, and control of parasites in the food chain, including an introduction to the topic from the perspectives of various issues surrounding foodborne parasites. The text then explores the different types of foodborne parasites, the dynamics of parasite transmission in different food sources, and the prevention and control of foodborne parasites in the food chain. Provides an overview of the occurrence, transmission, and control of parasites in the food chainExplores the differ.